2003
DOI: 10.21061/ijra.v4i1.1378
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Recirculation Sector of Finfish Aquaculture in the United States and Canada

Abstract: C h a r a c t e r i s t i c s o f t h e R e c i r c u l a t i o n S e c t o r o f F i n t i s hA q u a c u l t u r e i n t h e U n i t e d S t a t e s a n d C a n a d a J . D e l a b b i o 1 * , B . R . M u r p h y 1 , G . R . J o h n s o n 2 , E . H a l l e rm a n 1 1 V i r g i n i a P o l y t e c h n i c I n s t i t u t e a n d S t a t e U n i v e r s i t y D e p t . F i s h e r i e s a n d W i l d l i f e S c i e n c e s B l a c k s b u r g , V i r g i n i a 2 4 0 6 1 -0 3 2 1 U SA 2 F i s h P a t h o l o g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
2
5
0
1
Order By: Relevance
“…The quantitative study covered topics related to Themes 1 to 6 of the If a pig farmer is familiar with the clinical signs of CSF, he is in the best position to detect this disease, because he is on the frontline of animal disease identification and responsible for biosecurity measures. Our qualitative findings demonstrated that biosecurity behavior (practices employed on farms to prevent and/or control disease) are influenced by levels of awareness or knowledge about biosecurity, which is in line with previous research (Delabbio et al, 2003(Delabbio et al, , 2004(Delabbio et al, , 2005Lawson et al, 2001;Heffernan et al, 2008). Farmers' knowledge and awareness of the disease and their willingness to report the disease, was called vigilance towards disease by Hopp et al (2007).…”
Section: Questionnairesupporting
confidence: 89%
“…The quantitative study covered topics related to Themes 1 to 6 of the If a pig farmer is familiar with the clinical signs of CSF, he is in the best position to detect this disease, because he is on the frontline of animal disease identification and responsible for biosecurity measures. Our qualitative findings demonstrated that biosecurity behavior (practices employed on farms to prevent and/or control disease) are influenced by levels of awareness or knowledge about biosecurity, which is in line with previous research (Delabbio et al, 2003(Delabbio et al, , 2004(Delabbio et al, , 2005Lawson et al, 2001;Heffernan et al, 2008). Farmers' knowledge and awareness of the disease and their willingness to report the disease, was called vigilance towards disease by Hopp et al (2007).…”
Section: Questionnairesupporting
confidence: 89%
“…After 7 weeks of the culture, the final mean weight of shrimp was 33.91 ± 5.3 in T 1 and 34.38 ± 6.4 g in T 2 . Similar growth results have been reported by Tacon, Cody, Conquest, Divakaran, Forster & Decamp (2002), Cytryn et al (2003), Delabbio et al (2003), Copeland et al (2005), Gandy (2004), Gandy et al (2007), Kuhn et al (2007) and Green (2008).…”
Section: Discussionsupporting
confidence: 91%
“…The respondents to the survey, which had an 86% response rate, were the managers and owners of finfish recirculating facilities who identified business as their primary purpose (Delabbio et al 2003). Sixty-seven percent of respondents were from the United States (n ϭ 54) and 33% were from Canada (n ϭ 27).…”
Section: Background Of Survey Respondentsmentioning
confidence: 99%
“…In the past, poor biosecurity utilization on farms was assumed to result primarily from a lack of knowledge about biosecurity (Gillespie 2000;Sanderson et al 2000). However, research by Delabbio et al (2003) showed that managers and owners of finfish recirculation facilities in the United States and Can-ada generally had a high level of formal education, even while there was considerable range in the type and frequency of biosecurity practiced at their sites. In this earlier work, no statistically significant relationship was found between frequency of use of different biosecurity measures and owner/ manager level of education.…”
mentioning
confidence: 99%